Correlates of bushmeat in markets and depletion of wildlife. Issue 3 (7th January 2015) - Fa, Julia E.; Olivero, Jesus; Farfán, Miguel Á.; Márquez, Ana L.; Duarte, Jesús; Nackoney, Janet; Hall, Amy; Dupain, Jef; Seymour, Sarah; Johnson, Paul J.; Macdonald, David W.; Real, Raimundo; et al.
Abstract: We used data on number of carcasses of wildlife species sold in 79 bushmeat markets in a region of Nigeria and Cameroon to assess whether species composition of a market could be explained by anthropogenic pressures and environmental variables around each market. More than 45 mammal species from 9 orders were traded across all markets; mostly ungulates and rodents. For each market, we determined median body mass, species diversity (game diversity), and taxa that were principal contributors to the total number of carcasses for sale (game dominance). Human population density in surrounding areas was significantly and negatively related to the percentage ungulates and primates sold in markets and significantly and positively related to the proportion of rodents. The proportion of carnivores sold was higher in markets with high human population densities. Proportion of small‐bodied mammals (<1 kg) sold in markets increased as human population density increased, but proportion of large‐bodied mammals (>10 kg) decreased as human population density increased. We calculated an index of game depletion (GDI) for each market from the sum of the total number of carcasses traded per annum and species, weighted by the intrinsic rate of natural increase (rmax ) of each species, divided by individuals traded in a market. The GDI of a market increased as the proportion of fast‐reproducing species (highest rmax ) increased and as the representation of species with lowest rmax (slow‐reproducing) decreased. The best explanatory factor for a market's GDI was anthropogenic pressure—road density, human settlements with >3000 inhabitants, and nonforest vegetation. High and low GDI were significantly differentiated by human density and human settlements with >3000 inhabitants. Our results provided empirical evidence that human activity is correlated with more depleted bushmeat faunas and can be used as a proxy to determine areas in need of conservation action . Abstract : Correlaciones entre los Mercados de Carne de Animales Silvestres y la Disminución de la Vida Silvestre Resumen: Usamos datos numéricos de carcasas de especies de vida silvestre vendidas en 79 mercados de carne de animales silvestres, en una región de Nigeria y Camerún, para evaluar si la composición de especies de un mercado puede explicarse por medio de presiones antropogénicas y variables ambientales alrededor de cada mercado. Más de 45 especies de mamíferos de nueve órdenes fueron vendidas en todos los mercados, la mayoría ungulados y roedores. Para cada mercado determinamos el promedio de masa corporal, diversidad de especies (diversidad de presa) y taxones que principalmente contribuyeron al número total de carcasas en venta (dominancia de presa). La densidad de población humana en las áreas colindantes estuvo negativa y significativamente relacionada con el porcentaje de ungulados y primates vendidos en los mercados y positiva y significativamente relacionada con la proporción de roedores. La proporción de carnívoros vendidos fue más alta en los mercados con altas densidades de población humana. La proporción de mamíferos de pequeño tamaño (< 1kg) vendidos en los mercados se incrementó conforme se incrementaba la densidad de población humana, pero la proporción de mamíferos de gran tamaño (> 10kg) disminuyó conforme aumentó la densidad de población humana. Calculamos un índice de disminución de presas (IDP) para cada mercado, a partir de la suma del número total de carcasas vendidas por año y especie, sopesado por la tasa intrínseca de incremento natural ( r max ) de cada especie, dividida por el número de individuos vendidos en un mercado. El IDP de un mercado se incrementó conforme lo hizo la proporción de especies de rápida reproducción ( r max más alta) y conforme disminuyó la representación de especies con la r max más baja (de baja reproducción). El mejor factor explicativo para el IDP de un mercado fue la presión antropogénica – densidad de carreteras, asentamientos humanos con más de 3000 habitantes y vegetación no boscosa. Los IDP altos y bajos fueron significativamente diferenciados por la densidad humana y los asentamientos humanos con más de 3000 habitantes. Nuestros resultados proporcionaron evidencia empírica de que la actividad humana está correlacionada con la disminución de especies cazadas y puede usarse como indicador para determinar áreas que necesiten acciones de conservación.